2008
DOI: 10.1016/j.ejheart.2008.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Adequate energy‐protein intake is not enough to improve nutritional and metabolic status in muscle‐depleted patients with chronic heart failure

Abstract: Background: An adequate energy-protein intake (EPI) when combined with amino acid supplementation may have a positive impact on nutritional and metabolic status in patients with chronic heart failure (CHF). Methods and results: Thirty eight stable CHF patients (27 males, 73.5 ± 4 years; BMI 22.5 ± 1.4 kg/m 2 ), with severe depletion of muscle mass and were randomised to oral supplements of essential amino acids 8 g/day (EAA group; n = 21) or no supplements (controls; n = 17). All patients had adequate EPI (ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(132 citation statements)
references
References 47 publications
(67 reference statements)
2
122
1
4
Order By: Relevance
“…From a clinical perspective, this study confirms data obtained in previous investigations carried out in patients with COPD [8,9] or with chronic heart failure [10] who were supplemented with the same amino acid formula, at the same dose used in the present study. EAAs should not be intended as a substitute for Rehab whenever possible.…”
Section: B) Eaas and Quality Of Lifesupporting
confidence: 81%
See 1 more Smart Citation
“…From a clinical perspective, this study confirms data obtained in previous investigations carried out in patients with COPD [8,9] or with chronic heart failure [10] who were supplemented with the same amino acid formula, at the same dose used in the present study. EAAs should not be intended as a substitute for Rehab whenever possible.…”
Section: B) Eaas and Quality Of Lifesupporting
confidence: 81%
“…This hypothesis relies on the following considerations: firstly, EAAs, by promoting protein synthesis [7], can increase body mass (mainly the muscle portion) which plays a crucial role for the exercise performance and the perception of well-being. Secondly, preliminary studies carried out by two independent groups [8,9] have shown that EAA supplementation increases physical activity, cognition and quality of life in cachectic/sarcopenic COPD subjects, while another study found that EAAs can improve the nutritional state; the muscle metabolism, and the exercise capacity in individuals with chronic heart failure [10]. Furthermore, several studies found that EAAs work as precursors in the synthesis of brain neurotransmitters [11] which are involved in mood, behavioural motor activity, and cognition [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients had to be clinically stable since at least one month [8], have had a stable body weight over the preceding 3 months, and have an adequate daily protein (≥ 1.1 g/kg) and energy (≥30 kcal/kg) intake [7]. Particular attention was paid to adequate protein intake and normal EAA intake (≥30% total amino acid intake) ( Table 1).…”
Section: Study Populationmentioning
confidence: 99%
“…To be included into the study, patients should be at the best of their clinical and nutritional conditions with normal tissue insulin sensitivity (HOMA index b 2.4) [7], normal liver and renal function, and without contraindications to β-blocker use. Moreover, patients had to be clinically stable since at least one month [8], have had a stable body weight over the preceding 3 months, and have an adequate daily protein (≥ 1.1 g/kg) and energy (≥30 kcal/kg) intake [7].…”
Section: Study Populationmentioning
confidence: 99%
“…Therefore, nitrogen supply should not be calculated as the total nitrogen content that is the sum of EAs plus NEAs, but mainly the adequacy of EAs intake. Many pathological conditions increase dramatically nitrogen daily needs, coronary heart disease, 23 chronic obstructive pulmonary disease, 24 wound healing, 25 and traumatized and critically ill patients, 26 so that nitrogen intake is impossible to be matched by normal diets.…”
Section: Discussionmentioning
confidence: 99%